2001
DOI: 10.1007/s004390100490
|View full text |Cite
|
Sign up to set email alerts
|

Complete and rapid scanning of the cystic fibrosis transmembrane conductance regulator (CFTR) gene by denaturing high-performance liquid chromatography (D-HPLC): major implications for genetic counselling

Abstract: More than 900 mutations and more than 200 different polymorphisms have now been reported in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. Ten years after the cloning of the CFTR gene, the complete scanning of the 27 exons to identify known and novel mutations remains challenging. Rapid accurate identification of mutated alleles is important for prenatal diagnosis, for cascade screening in families at risk of cystic fibrosis (CF) and for understanding the correlation between genotype and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 40 publications
0
93
0
6
Order By: Relevance
“…4 Every mutant discovered by these methods was sequenced with the ABI PRISM 377 or 310 Sequence Analyser. Some variants have been studied, on a fraction of the total sample, with a restriction enzyme specific method: the following cSNSs numbered as in Table A1, nos.…”
Section: Mutation Analysismentioning
confidence: 99%
“…4 Every mutant discovered by these methods was sequenced with the ABI PRISM 377 or 310 Sequence Analyser. Some variants have been studied, on a fraction of the total sample, with a restriction enzyme specific method: the following cSNSs numbered as in Table A1, nos.…”
Section: Mutation Analysismentioning
confidence: 99%
“…Estimates of allele diversity are bracketed between two extremes: they would be minimal if all unknown mutations in a population were, in fact, the same allele, and they would be maximal if all unknown mutations were different from each other. Intensive mutation-detection efforts by means of denaturing high-performance liquid chromatography 27 have shown that chromosomes bearing previously unknown mutations carried each a new, different, unique mutation. Thus, it is likely that the 'unknown' portion of the mutation spectrum contains a wide diversity of alleles.…”
Section: Genetic Diversity Estimatesmentioning
confidence: 99%
“…This variation eludes common PCRbased techniques for mutation detection in this region, including direct sequencing, as well as denaturing highperformance liquid chromatography. Thus, if denaturing high-performance liquid chromatography analysis is used, it is necessary to use primers that have been documented 7 to prevent the variability that T/TG repeats can cause. Using this method, however, only the beginning of exon 9 is amplified.…”
mentioning
confidence: 99%